IMPROVING FINANCIAL TECHNOLOGIES IN CENTRAL ASIA COUNTRIES (World Economics and Finance Bulletin, 2024)
This article is devoted to analysis of the process of implementing several financial technologies, adapted to the current condition of Central Asian countries. The provision of relevant financial services during the pandemic was jointly provided by fintech companies and banks, which launched payment services similar to fintechs. This also is considered to be essential point of the article
Keywords: SME; fintech; financial services